#20 A Study on defensive effects of ferulic acid against neuronal inflammation persuaded by Cyclophosphamide - Mishra, Tejesvi; Kumar, Vinay (Journal of Pharmaceutical Chemistry, 2022)
Neurotoxicity, which occurs due to progressive neuronal inflammation, is one of the globally leading challenges for clinical science nowadays. There are so many drugs that cause an inflammatory response to the nervous system as their adverse effects can result in critical complications to the patients. One such drug is Cyclophosphamide, a well-known anticancer and immunosuppressant drug. Cyclophosphamide and its metabolite (acrolein) have been proposed to be highly lipophilic moiety, cross the blood-brain barrier (BBB) and exhibit significant neurotoxicity. However, as of now, no adjuvant is available to mitigate this neurotoxic manifestation. Therefore, in the present study, ferulic acid (FRA) has been explored for possible neuroprotective effects against Cyclophosphamide-induced neurotoxicity in the Swiss Albino mice. Animals were divided into five groups (n=6) and treated with FRA for fourteen days and single-dose Cyclophosphamide was administered on the seventh day. Animals were subjected to neurobehavioral tests such as the Forced Swim Test (FST) and Morris Water Maze (MWM) test. On day fifteenth, animals were sacrificed and the brain was removed and used for biochemical analysis including parameters like antioxidant enzymes (SOD, CAT, GSH), lipid peroxidation, and pro-inflammatory cytokines. Treatment with FRA significantly reversed these behavioral and biochemical markers towards normal and mitigated Cyclophosphamide-induced neurotoxic manifestation. However, more detailed studies are needed to bring FRA from bench to bedside that it can be used as an adjuvant among chemotherapeutically treated patients.